Environmental and Emission Analysis of Biodiesel/Bioethanol/Nanoparticles Blends With Hydrogen Addition in Diesel Engine - Ravikumar Jayabal; Rajkumar Sivanraju (Energy Science & Engineering)
ABSTRACT This study investigates the emission characteristics of a diesel engine fueled by a combination of algae biodiesel (AB), bioethanol (BE), graphene oxide (GO) nanoparticles, and hydrogen (H2) fumigation, assessing their potential as sustainable fuel alternatives. A single‐cylinder diesel engine was tested under different load conditions using a biodiesel blend (AB + GO 50 ppm + BE 10%) as the primary fuel. At the same time, H2 was introduced into the intake manifold via a port fuel injector at flow rates of 3 and 6 L/min (LPM). Emissions, including hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx), and smoke opacity, were analyzed. Emission data from three independent runs at each load were analyzed with one‐way ANOVA followed by Tukey's HSD test (p < 0.05) to verify statistical significance. The findings showed that H2 fumigation at 3 and 6 LPM reduced HC emissions by 33.33% and 46.66%, CO by 57.75% and 77.58%, and smoke opacity by 15.04% and 31%, respectively, when compared with conventional diesel. While NOx emissions for the biodiesel blend without H2 were 11.69% lower than diesel, H2 fumigation increased NOx by 20.71% and 39% at 3 and 6 LPM, respectively. Combining AB, BE, GO, and H2 effectively reduces HC, CO, and smoke emissions while improving combustion efficiency. However, higher NOx emissions with H2 fumigation highlight the need for further optimization.